Effect Of Combination Of Snakehead Fish Extract (Channa Striata), Meniran (Phyllanthus Niruri L.), And Temulawak (Curcuma Xanthorrhiza) On Histopathological and Liver Function Of Rats Model Diabetes Mellitus with High Fat Diet - Apmarda Simarmata, Tesalonika; Yulizal, OK; Sopacua, Erwin (Syntax Corporation Indonesia, 2024)
Diabetes mellitus is one of the metabolic disorders characterized by a progressive decrease in insulin sensitivity, resulting in hyperglycemia which causes oxidative stress and damage to liver function. Currently, anti-fibrogenic treatment options are still limited, This study aims to determine the effect of capsules containing a combination of snakehead fish extract (Channa striata), meniran (Phyllanthus niruri L.), and curcuma (Curcuma xantorrhiza) on a high fat diet of diabetic melitus model rats. This type of research is an experimental laboratory in vivo with a randomized post test-only control group design. The population of this study is male rats (Rattus norvegicus) of the wistar strain with a sample size of 30 mice divided into 5 groups of rats. Data analysis used the SPSS version 26 program which was analyzed by the Kruskal-Wallis and Mann-Whitney statistical tests. The results of this study found that there was a difference but not significant between SGOT and SGPT between all groups (p>0.05). Therefore, from these results, it can be stated that there is an effect of capsules containing a combination of snakehead fish extract (Channa striata), meniran (Phyllanthus niruri L.), and curcuma (Curcuma xantorrhiza) in diabetic mellitus model rats with a high fat diet in improving liver function. It is hoped that further researchers can continue this research by using a combination of snakehead fish extract (Channa striata), meniran (Phyllanthus niruri L.), and curcuma (Curcuma xantorrhiza) in repairing damage to other organs other than the liver as a result of diabetes mellitus complications.